Occurrence of Paradiplozoon spp. in vimba bream Vimba vimba from Lake Köyceğiz, southwest Türkiye, with new data on their distribution - Emre Nesrin; Aydogdu Nurten; Aydogdu Ali; Emiroglu Özgür (Oceanological and Hydrobiological Studies)
Only one species of the genus Paradiplozoon (Akmerov 1974) has so far been recorded in Vimba vimba (Linnaeus, 1758) from Türkiye. This study was planned to improve the recording of the occurrence of diplozoids in V. vimba from a pristine area in a different geographical region. A total of 397 specimens of V. vimba were collected from Lake Köyceğiz by commercial fishermen over a period of one year and examined for the presence of diplozoids. Only one species of Paradiplozoon was found. Following a detailed morphological examination, the species was identified as Paradiplozoon bliccae (Reichenbach-Klinke 1961), which was subsequently confirmed by molecular data. A total of 1025 specimens of P. bliccae infected 185 of the 397 Vimba vimba specimens examined, with prevalence, mean intensity and abundance of 46.6%, 5.5 ± 4 parasites/fish, 2.5, respectively. The highest prevalence and mean abundance were determined in spring, while mean intensity values were higher in summers. Female hosts showed higher prevalence, mean intensity and mean abundance than males.